Two chaperones locked in an embrace: structure and function of the ribosome-associated complex RAC - Zhang, Ying; Sinning, Irmgard; Rospert, Sabine (Nature structural & molecular biology, 2017)
Chaperones, which assist protein folding are essential components of every living cell. The yeast ribosome-associated complex (RAC) is a chaperone that is highly conserved in eukaryotic cells. The RAC consists of the J protein Zuo1 and the unconventional Hsp70 homolog Ssz1. The RAC heterodimer stimulates the ATPase activity of the ribosome-bound Hsp70 homolog Ssb, which interacts with nascent polypeptide chains to facilitate de novo protein folding. In addition, the RAC-Ssb system is required to maintain the fidelity of protein translation. Recent work reveals important details of the unique structures of RAC and Ssb and identifies how the chaperones interact with the ribosome. The new findings start to uncover how the exceptional chaperone triad cooperates in protein folding and maintenance of translational fidelity and its connection to extraribosomal functions.